Effect of Fatty Acid Unsaturation on Gel Properties of Hairtail Myosin - Hongbo MI; Yaling LI; Zhenghan LI; Shumin YI; Jianrong LI; Mingli WANG; Xiaohua GUO; Xiaomin ZHOU; Jianyang YU (Shipin gongye ke-ji, 2023)
In order to investigate effects of fatty acid unsaturation on the gel properties of myosin, four kinds of fatty acids (stearic acid, oleic acid, linoleic acid, and α-linolenic acid) with different saturation was added into hairtail myosin. The changes of gel strength, water holding capacity, chemical forces, rheological properties, gel electrophoresis and protein secondary structure of myosin were analyzed. The results showed that gel strength and water holding capacity of myosin increased first and then decreased with the increasing of fatty acid unsaturation. The gel strength and water holding capacity of myosin-linoleic acid composite system were the highest, increasing by 59.73% and 15.73% compared with control group, respectively. The results of the rheological and electropherogram indicated that the storage modulus (G') and loss modulus (G'') of myosin containing fatty acids were higher than that of control group. The G' and G'' increased first and then decreased with the increasing of fatty acid unsaturation, and reached the maximum value in the myosin-linoleic acid group. However, there was no significant change in protein composition among all the groups. Infrared spectroscopy showed that the unsaturation of fatty acid had no obvious effect on the molecular backbone of myosin, but stearic acid, oleic acid, and linoleic acid promoted the conformation transform of myosin to irregular direction. In summary, fatty acid unsaturation had a significant effect on the gel properties of myosin, and linoleic acid was the best at improving the gel properties of hairtail myosin.